PERSPECTIVE ON CODE SWITCHING IN CONTENT-BASED CLASSROOMS: GOVERNMENT SCHOOLS CONTEXT IN PAKISTAN - Saeed, Rabea; Kashif, Saadia (PEOPLE: International Journal of Social Sciences, 2019)
Teaching in Pakistan has always shown irregular policy decisions with reference to medium of instructions, and choice of language used by teachers and students. This has resulted in below average education quality in government schools. Multitude of research has been done, both internationally and nationally, on use of language for teaching and learning. Using language repertoire of a learner has been found useful and effective for development and learning (Manan et al., 2017, Liebscher & Dailey, 2005). With recent trend towards code switching by declaring EMI as a challenge (p.47, National Education Policy Report, 2017), the paper aims at mapping teachers’ perspective on the policy. This is achieved through a questionnaire and series of interviews on code switching developed on patterns of Translanguage theory (García & Lin, 2017, García & Wei, 2014). By considering translanguaging, the pedagogic counterpart of code switching, the research provides direction and suggests a solution to a national problem that is which language to use for teaching and communication in government schools for effective teaching and learning.